Financing local enterprises. - Goh, Shane Shan. (2008)
Despite strong calls for entrepreneurship by the government, businesses still struggle to survive because of the lack of cash. Thus, we aim to help these businesses to achieve the financing they need by exploring the various avenues of financing, the problems faced by them and ways to counter these problems.